Penerapan Akad Wadiah Yad Dhamanah dalam Tabungan Sekolah - Mutmainnah, Mutmainnah; Susanti, Susanti; M. Holil Baita Putra (Al Rikaz: Jurnal Ekonomi Syariah, 2024)
Implementation of children's savings provided by the school with daily savings without limiting the minimum amount to be saved. So that it makes it easier for the guardians of students and students to set aside or save their money according to their desired targets and needs. This research uses a qualitative approach because the data collected is in the form of words and images. The implementation of children's savings at Madrasah Al-Amin applies to all female students starting from class 0-VI and they are required to have a savings book. This was also expressed by Ustadzah Hoiriyah in his interview that the requirements for being able to save are: "having a savings book and having to wait in line at al-Amin". The school savings contract used at Madrasah Al-Amin is an agreement to deposit funds from the customer to the school as the entrusted recipient of the deposit with the aim of maintaining the safety, security and integrity of the funds.